EDUKASI PENGGUNAAN APLIKASI PEDULI LINDUNGI DALAM MENGHADAPI KEHIDUPAN NEW NORMAL DI DESA SUKARAJA BARU - Ardiansyah, Arif (Lembaga Penelitian dan Pengabdian Masyarakat STISIPOL Candradimuka Palembang, 2020)
Welcoming the new normal and with the launch of the Pedulilindungi application by the Government of the Republic of Indonesia, Sukaraja Baru Village, Suda Indralaya, Ogan Ilir Regency, is one of the villages implementing guidelines for implementing new normal activities. The use of this application is part of what must be done in some public spaces. The socialization of this application by village officials encouraged the PKM team to become trainers so that it was easier to understand how to use it. From the one-day training and evaluation activities, the PKM team concluded that the participants were ready to successfully use this application in the new normal life in the village.